Cardiovascular diseases prediction by machine learning incorporation with deep learning - Subramani, Sivakannan; Varshney, Neeraj; Anand, M. Vijay; Soudagar, Manzoore Elahi M.; Al-keridis, Lamya Ahmed; Upadhyay, Tarun Kumar; Alshammari, Nawaf; Saeed, Mohd; Subramanian, Kumaran; Anbarasu, Krishnan; Rohini, Karunakaran (Frontiers in Medicine, 2023)
It is yet unknown what causes cardiovascular disease (CVD), but we do know that it is associated with a high risk of death, as well as severe morbidity and disability. There is an urgent need for AI-based technologies that are able to promptly and reliably predict the future outcomes of individuals who have cardiovascular disease. The Internet of Things (IoT) is serving as a driving force behind the development of CVD prediction. In order to analyse and make predictions based on the data that IoT devices receive, machine learning (ML)is used. Traditional machine learning algorithms are unable to take differences in the data into account and have a low level of accuracy in their model predictions. This research presents a collection of machine learning models that can be used to address this problem. These models take into account the data observation mechanisms and training procedures of a number of different algorithms. In order to verify the efficacy of our strategy, we combined the Heart Dataset with other classification models.